2020
DOI: 10.1177/0265407520964866
|View full text |Cite
|
Sign up to set email alerts
|

“Mom, dad, look at me”: The development of the Parental Phubbing Scale

Abstract: The widespread diffusion of smartphones has opened new challenges regarding the psychological consequences of their usage on social relationships. The term phubbing (a combination of phone and snubbing) indicates the act of ignoring someone in a social context by paying attention to the smartphone. The few existing studies show that phubbing is widespread, mutually reinforced, and socially accepted, with possible negative consequences for social and individual well-being. Phubbing can occur in every social con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 55 publications
3
21
1
4
Order By: Relevance
“…Spending excessive energy and time on mobile phones, they tend to neglect their children’s feelings ( Jiang et al, 2021 ). Numerous studies have demonstrated that parental phubbing behaviors have a detrimental effect on the parent–child relationship ( Xie et al, 2019 ; Niu et al, 2020 ; Pancani et al, 2020 ; Liu K. et al, 2021a , b ), reducing the quality of parenting ( Qu et al, 2020 ) and possibly resulting in teenagers developing negative emotions such as depression ( Liu J. et al, 2021 ), loneliness ( Geng et al, 2021 ), and internalizing problems ( Wang et al, 2020 ). Apart from that, adolescents may be at an increased risk of internet addiction and mobile phone use as a result of parental phubbing ( Hong et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Spending excessive energy and time on mobile phones, they tend to neglect their children’s feelings ( Jiang et al, 2021 ). Numerous studies have demonstrated that parental phubbing behaviors have a detrimental effect on the parent–child relationship ( Xie et al, 2019 ; Niu et al, 2020 ; Pancani et al, 2020 ; Liu K. et al, 2021a , b ), reducing the quality of parenting ( Qu et al, 2020 ) and possibly resulting in teenagers developing negative emotions such as depression ( Liu J. et al, 2021 ), loneliness ( Geng et al, 2021 ), and internalizing problems ( Wang et al, 2020 ). Apart from that, adolescents may be at an increased risk of internet addiction and mobile phone use as a result of parental phubbing ( Hong et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“… 17 Researchers have found that both phubbing behavior and smartphone addiction have social impairment on individuals, especially on interpersonal relationships, 2 , 14 such as in employer-employee relationships in the workplace, 18 romantic relationships, 19 and parent-child interaction in the family. 20 However, in contrast with smartphone addiction, phubbing behavior has become a socially acceptable behavior 14 that is much more devious and pervasion. The addiction literature boomed before phubbing became prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…Phubbing causes various problems in family communication. Researchers have identified the following problems caused by parental phubbing when parents interact with their children; academic burnout (Bai et al, 2020a), feelings of disconnection (Pancani et al, 2020),lower life satisfaction (Liu et al, 2020a), lowerself esteem (Hong et al, 2019;Wang et al, 2020a), parent-child attachment problems (Xie et al, 2019), problematic mobile phone use and mobile phone dependency (Fu et al, 2020;Liu et al, 2019;Niu et al, 2020;Xie et al, 2019;Zhang et al, 2021), internet gaming disorder (Xie et al, 2021), cyberbullying (Wang et al, 2020b), social anxiety (Zhang et al, 2021), neuroticism (Bai et al, 2020a), depressive symptoms (Bai et al, 2020b;Wang et al, 2020a ;Xie & Xie, 2020;Xie et al, 2021). Research on the effects of parental phubbing on child and adolescent behavior should be supported.…”
Section: Parent and Phubbingmentioning
confidence: 99%